2022
DOI: 10.7196/sajch.2022.v16i4.1900
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings and the clinical characteristics of children with cerebral palsy at a public sector hospital in Gauteng Province, South Africa

Abstract: Background. Cerebral palsy (CP) is a common cause of physical impairment in children. Brain magnetic resonance imaging (MRI) can define different neuropathological patterns of brain injury in CP. There are limited data available on MRI findings of children with CP in Africa.  Objective. To describe the clinical characteristics, risk factors and MRI findings of children with CP attending a developmental clinic at a tertiary hospital in South Africa; and to assess possible associations between the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In 2016, the Surveillance of Cerebral Palsy in Europe (SCPE) group introduced the MRI classification system (MRICS), which has been validated as both applicable and reliable for communication across various CP registers ( 3 ). Subsequently, multiple studies have explored the relationship between MRICS patterns and CP type, functional impairment, and comorbidities, yielding inconsistent conclusions ( 4 8 ). For example, most studies have identified white matter injury as the most common type, whereas in Africa it was grey matter injury because the main etiology of CP there were birth asphyxia and bilirubin encephalopathy ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, the Surveillance of Cerebral Palsy in Europe (SCPE) group introduced the MRI classification system (MRICS), which has been validated as both applicable and reliable for communication across various CP registers ( 3 ). Subsequently, multiple studies have explored the relationship between MRICS patterns and CP type, functional impairment, and comorbidities, yielding inconsistent conclusions ( 4 8 ). For example, most studies have identified white matter injury as the most common type, whereas in Africa it was grey matter injury because the main etiology of CP there were birth asphyxia and bilirubin encephalopathy ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, multiple studies have explored the relationship between MRICS patterns and CP type, functional impairment, and comorbidities, yielding inconsistent conclusions ( 4 8 ). For example, most studies have identified white matter injury as the most common type, whereas in Africa it was grey matter injury because the main etiology of CP there were birth asphyxia and bilirubin encephalopathy ( 8 ). Unilateral spastic paralysis was associated with grey matter injury, but it was more common in white matter injury in Horber's study ( 4 ).…”
Section: Introductionmentioning
confidence: 99%